Timeline of Palmer amaranth (Amaranthus palmeri) invasion and eradication in Minnesota. (29th October 2021) - Yu, Eric; Blair, Shane; Hardel, Mari; Chandler, Monika; Thiede, Denise; Cortilet, Anthony; Gunsolus, Jeffrey; Becker, Roger
Abstract: Palmer amaranth–a fast-growing, challenging-to-control noxious weed that significantly reduces crop yields—was first found in Minnesota in September 2016 in conservation plantings sown with Palmer amaranth contaminated seed mixes. Minnesota Department of Agriculture (MDA) designated Palmer amaranth as a Prohibited Noxious Weed in 2015 and listed it as a Noxious Weed Seed in 2016 by emergency order. A genetic test to identify Palmer amaranth was simultaneously developed by multiple laboratories, providing a tool to limit its spread as a contaminant in seed. Seed companies adopted genetic testing methods for labeling seed for sale, thus reducing introductions via the seed pathway. Additionally, MDA determined that manure spread on crop fields from contaminated screenings fed to livestock resulted in new infestations. Limiting spread via these and other potential pathways was critical to successfully reducing the impact of Palmer amaranth. MDA, University of Minnesota (UMN) Extension, Conservation Corps Minnesota and Iowa (CCMI), farmers, and other partners are working to eradicate these infestations before they can spread. In 2016, 35 sites were sown with Palmer amaranth–contaminated seed mixes. Palmer amaranth was found at eight (23%) of these sites. Management with intensive scouting, torching, prescribed burning, and herbicide application was implemented in 2016 and 2017. By 2018, no Palmer amaranth was found at any of these sites. Similar success to newer infestations in 2018, 2019, and 2020 was achieved using the same methods. MDA recorded management activities and documented a comprehensive timeline of Palmer amaranth in Minnesota. This timeline provides a story of success and challenges in combating and eradicating Palmer amaranth.